Clinical features of multiple myeloma with bone plasmacytomas - E. A. Mamaeva; M. V. Soloveva; M. V. Solovev; A. M. Kovrigina; T. P. Danilina; L. P. Mendeleeva (Онкогематология)
Background. Multiple myeloma (MM) is a plasma cell tumour, which could be followed by formation of bone plasmacytomas. Bone plasmacytoma is plasma cells proliferate, developed in a medullar cavity, which could destroy cortical layer of a bone and escape to the surrounding tissues. Biological characteristics of tumour substrate hypothetically could influence the clinical course of MM.Aim. To compare clinical and laboratory parameters of newly diagnosed MM depending on the presence or absence of bone plasmacytomas.Materials and methods. A retrospective study included 40 patients with newly diagnosed MM aged from 24 to 63 years. 21 patients are diagnosed with bone plasmacytomas. In another 19 patients MM proceeded without plasmacytomas. As an induction therapy all patients were treated with bortezomib-containing regimens. 10 patients were also received immunomodulatory drugs. 34 patients underwent autologous hematopoietic stem cell transplantation (auto-HSCT).Results. When comparing laboratory parameters at the onset of MM, patients with bone plasmacytomas showed minor lesion of bone marrow, higher haemoglobin concentration and low paraprotein secretion. When comparing MM clinical parameters it turned out that the frequency of achieving a significant antitumor response after induction therapy was reliably lower in patients with bone plasmacytomas: 28.6 % versus 68.4 % (p = 0.038). Auto-HSCT made it possible to deepen the antitumor response in group of patients with bone plasmacytomas. On +100 day auto-HSCT significant antitumor response was registered in 52.6 % of patients. For correct assessment of antitumor response the dynamics of plasmacytoma measurements is very important. When using only the data of immunochemical analysis for response assessment, the frequency of achieving a significant antitumor response is overestimated, this is not an adequate reflection of clinical situation.Conclusion. MM with bone plasmacytomas has some clinical and laboratory features. Auto-HSCT is highly efficient method of treatment of this patient cohort. Assessment of antitumor response in patients with bone plasmacytomas only by the data of immunochemical analysis is insufficient and may serve as a reason for choosing the wrong therapeutical tactics.